Persepsi siswa sekolah menengah atas dan kejuruan tentang dialog antarumat beragama - Rochim, Ahmad Abdul; Sirait, Sangkot; Arif, Mahmud (Al-Liqo: Jurnal Pendidikan Islam, 2025)
Interreligious dialogue (IRD) is a crucial pillar in fostering tolerance and social harmony educational environments. This research is motivated by the importance of students’ understanding of IRD as presented in religious education curricula. The research problem addressed is how students perceive the IRD material and to what extent they apply it in their daily lives. The aim of this study is to examine the perceptions of 12th-grade students toward IRD material and to measure the extent to which dialogical attitudes are practiced in their interactions. A quantitative survey method was employed by distributing questionnaires at a senior high school. The findings reveal that the majority of respondents have a positive perception of IRD and reported having received the material through classroom instruction. The data also indicates that students not only understand the concept theoretically but also apply it in their everyday lives. This is evidenced through the stages of behavior change approach, which shows that most students are in the action and maintenance stages in implementing dialogical attitudes both in school and outside. This study contributes to strengthening the role of schools in instilling religious tolerance values and demonstrates the effectiveness of IRD education.